2010
DOI: 10.1002/ange.201001188
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Asymmetric Addition of Alkyne CH Bonds across 1,3‐Dienes Using Taddol‐Based Chiral Phosphoramidite Ligands

Abstract: Much interest has been focused on the catalytic, direct conversion of alkyne C À H bonds through C À C bond-forming reactions without the stoichiometric generation of acetylides. [1] One of the most widely used procedures for such an atom-economical process is the nucleophilic alkynylation of carbonyl compounds, a,b-unsaturated carbonyl compounds, or related electrophiles, in which catalytically generated metal acetylides often play a key role. [2, 3] Recent attention has focused on the development of asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The semi-hydrogenation of alkyne (5a) by DIBAL-H (diisobutylaluminum hydride) could be highly stereoselective, giving the Z-alkene (9). In addition, oxidative cleavage of the triple bond in 5e could afford the corresponding chiral carboxylic acid (10).…”
Section: Discussionmentioning
confidence: 99%
“…The semi-hydrogenation of alkyne (5a) by DIBAL-H (diisobutylaluminum hydride) could be highly stereoselective, giving the Z-alkene (9). In addition, oxidative cleavage of the triple bond in 5e could afford the corresponding chiral carboxylic acid (10).…”
Section: Discussionmentioning
confidence: 99%
“…Later the same group (Nishimura and Hayashi) developed a cobalt‐Josiphos‐type catalyst system for handling substrates without such a neighboring coordinating group 10. In 2010, Suginome showed the first nickel‐catalyzed asymmetric addition of a terminal alkyne CH bond to 1,3‐dienes 11. The trans ‐configuration of the dienes and unique α‐siloxy‐α,α‐ sec ‐alkyl‐containing alkynes were found to be crucial reaction partners for achieving high enantioselectivity.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the allene moiety had to contain the coordinating diphenylphosphinyl group (P(O)Ph 2 ). In 2010, Shirakura and Suginome pioneered the nickel‐catalyzed enantioselective addition of the CH bond of a terminal alkyne across a 1,3‐diene (Scheme ) 9. The trans diene was demonstrated to be crucial for obtaining high enantioselectivity (up to 93 % ee ) and reactivity.…”
Section: Methodsmentioning
confidence: 99%